The Role of External Assurance in Enhancing the Credibility of Sustainability Reports - Jessica Laurenza Manik; Nayla Zahiya Syifa; Yusnaini Yusnaini (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
This study examines the role of external assurance in strengthening the credibility of sustainability reports using a qualitative systematic literature review (SLR) approach. A total of 30 peer-reviewed journal articles published between 2020 and 2026 and indexed in Scopus were analyzed based on predefined criteria, including relevance to external assurance in sustainability or ESG disclosure, English language, and full-text availability. The findings indicate that external assurance predominantly exerts a positive and substantive impact on reporting credibility. Specifically, 22 out of 30 studies report that assurance enhances disclosure quality, strengthens governance mechanisms, reduces information asymmetry, improves firm value, and increases stakeholder trust. These results are consistent with Stakeholder Theory, Agency Theory, and Legitimacy Theory, which position assurance as a mechanism of accountability, monitoring, and legitimacy building. However, 8 studies highlight symbolic or limited effects, particularly when assurance scope is constrained or regulatory frameworks are weak. Overall, external assurance demonstrates strong potential to enhance sustainability reporting credibility, although its effectiveness depends on regulatory quality, assurance standards, and corporate governance strength.